Acute Phase Protein Response and Polymorphonuclear Leukocyte Cathepsin G Release After Slow Interleukin-1 Stimulation in the Rat - Peter Björk; Thorarinn Gudmundsson; Kjell Ohlsson (Mediators of Inflammation)
In this work we have studied the acute phase protein response and degranulation of polymorphonuclear leukocytes in vivo in the rat after a slow interleukin-1β stimulation. A total dose of 1 μg, 2 μg, 4 μg and 0 μg (controls with only vehicle) of interleukin-1β was released from osmotic minipumps over a period of 7 days. The pumps were implanted subcutaneously. A cystic formation was formed around the pumps that contained interleukin-1β whereas no tissue reaction was seen around pumps containing only vehicle. Besides flbroblasts the cyst wall contained numerous polymorphonuclear leukocytes which were positively stained for cathespin G. α2-macroglobulin, α1-inhtbitor-3, α1-proteinase inhibitor, albumin and C3 were measured by electroimmunoassay and all showed plasma concentration patterns that were dose-dependent to the amount of interleuktn-1β released. Fibrinogen in plasma was elevated in the control group but showed decreased plasma values with higher doses of interleukin-1β released. All animals showed increased plasma levels of cathespin G but the lowest levels for cathespin G were seen for the highest interleukin-1β dose released. It was clearly seen that a slow continuous release of interleukin-1β in vivo caused an inflammatory reaction. Plasma levels for the proteins analysed all showed a similar pattern, namely an initial increase or decrease of plasma concentration followed by a tendency to normalization of plasma values. It was concluded that a long-term interleukin-1β release could not sustain the acute phase protein response elicited by the initial interleukin-1β release.